The Effects of Insecticide Treated Netting on Male-Female Interactions in Red Flour Beetles - Hesseltine, Elise; Gerken, Alison (My University, 2018)
Courtship behaviors take place before and after copulation for the purpose of stimulating the female (Evardsson & Arnqvist 2000). Females will mate with different males within minutes of the first copulation (Pai &Yan 2003), with males showing a preference for virgin females (Lewis & Iannini 1995). Red flour beetles (Tribolium castaneum) show a decrease in progeny output following exposure to insecticide treated netting (Scheff et al. in prep). To assess whether females exposed to insecticide treated netting had decreased courtship attempts, virgin females were placed with a single male to accurately determine the number of mating pair interactions. Courtship behavior and mating pair interactions were recorded to determine if the number of mating pair interactions will decrease after exposure to insecticide treated netting. Our results indicate no significant difference between the number of interactions between females exposed to control netting or insecticide treated netting. However, with females exposed to insecticide treated netting the duration of interactions increased and more interactions were initiated by males. These results suggest that the decline in progeny output may be due to reallocation of reproductive resources following exposure to insecticide treated netting and not due to decreased numbers of mating attempts.
Keywords: Fall 2018